1997
DOI: 10.1002/eji.1830270946
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of LFA‐1‐mediated T cell adhesion induced by the HIV envelope glycoprotein gp160 requires phosphatidylinositol‐3‐kinase activity

Abstract: Human immunodeficiency virus binds to CD4+ T lymphocyte by the interaction, in part, between its gp120 envelope glycoprotein and the CD4 molecule. We and others have reported that the lipid kinase phosphatidylinositol-3-kinase (PI3-kinase) is associated with the CD4-p56lck complex and can be activated by various CD4 ligands. In a previous report we showed that the gp160 envelope down-regulates lymphocyte function-associated antigen-1 (LFA-1)-dependent adhesion between CD4+ T cells and B cells. This down-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recently, Francois and Klotman [42] reported that gp120 induced PI-3K activation in primary macrophages and that it was necessary for viral replication. Others have shown that PI-3K activation by HIV-1 Env, Nef, or Tat is necessary for optimal viral replication, MHC class I down-regulation, and regulation of apoptosis in infected cells [43][44][45][46][47]. In contrast, we sought to investigate the effects of gp120 apart from viral infection, as cells may be exposed to Env on noninfectious virions or shed from virus or infected cells, and evidence in vivo suggests that uninfected macrophages, as well as infected cells, are activated and produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Francois and Klotman [42] reported that gp120 induced PI-3K activation in primary macrophages and that it was necessary for viral replication. Others have shown that PI-3K activation by HIV-1 Env, Nef, or Tat is necessary for optimal viral replication, MHC class I down-regulation, and regulation of apoptosis in infected cells [43][44][45][46][47]. In contrast, we sought to investigate the effects of gp120 apart from viral infection, as cells may be exposed to Env on noninfectious virions or shed from virus or infected cells, and evidence in vivo suggests that uninfected macrophages, as well as infected cells, are activated and produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme phosphorylates the D-3 position of the inositol ring of phosphatidylinositol (PI), phosphatidylinositol 4-phosphate (PI 4-P), and phosphatidylinositol 4,5-bisphosphate (PI 4,5-P 2 ) (7). These phospholipids are one of the intermediary messengers for the CD4-mediated down-regulation of LFA-1-dependent adhesion since inhibitors of PI3-kinase activity abrogate the regulatory event (8). The mechanism by which PI3-kinase upon CD4 ligand binding mediates down-regulation of LFA-1 adhesion is unknown.…”
mentioning
confidence: 99%
“…Several reports indicate that SHP1 regulates the phosphorylation of p85␣ (27,29). We first confirmed that SHP1 regulates phosphorylation of p85␣ by comparing the patterns of p85␣ phosphorylation in HEK293-T2 cells transfected with wild type SHP1 or with empty vector.…”
Section: Impdhii Inhibits Nf-b Activity Following Tlr2mentioning
confidence: 52%